Analysis of Interrelations of Scientific Subject Areas Based on the Method of Graphosemantic Modeling - Egorova, A. D.; Amurskaya, O. Yu (Automatic documentation and mathematical linguistics, 2025)
This article explores the unification of two relevant areas that are rarely studied together: the computational linguistics field of sentiment analysis and the physico-mathematical field of entropy-complexity. Based on keywords from articles on both topics, links are established that form a single semantic space at the junction of these subject areas. The information system of the data visualization tool Semograph was used to visualize the data and identify semantic links between semantic components and between sentiment analysis and entropy complexity.